(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
“Locality 84” is a new Konservat-Lagerstätte from the Friuli Carbonate Platform (NE Italy) preserving articulated fish skeletons and plant fossils. The fossil assemblage was collected in a carbonate olistolith of one of the megabeds characterising the upper Palaeocene-lower Eocene Grivò Flysch Formation in the Julian Prealps. Fish remains are dominant, but plant fossils form one third of the assemblage. The Late Cretaceous age of the “locality 84” olistolith is supported by the presence of the conifer Frenelopsis along with a plant fossil assemblage dominated by angiosperm leaves, by the rarity of acanthomorph teleosts represented by primitive forms and by the presence of pycnodontine pycnodontiforms. Further evidence (e.g., the affinity of some angiosperm leaves) suggests a Campanian-Maastrichtian age. The fossil assemblage differs from other similar fossil assemblages from the Cretaceous of the Friuli Carbonate Platform due to the extreme rarity of both shelled and non-shelled invertebrates, rarity of conifer shoots, a dominance of pycnodontiforms and basal non-acanthomorph teleosts (elopiforms, gonorhynchiforms, pachyrhizodontoids and putative albuliforms) in the ichthyofauna, with few acanthomorphs, no clupeomorphs, and no needlefish-like aulopiforms and chondrichthyans. The environment of deposition of the sediments containing the fossils may be a tidal flat or a restricted water body in the inner part of the Friuli Carbonate Platform but with a connection to the open sea.